A Proof-of-Mechanism Study to Test Effects of the NMDA Receptor Antagonist Lanicemine on Behavioral Sensitization in Individuals With Symptoms of PTSD - Lijffijt, Marijn; Green, Charles E.; Balderston, Nicholas; Iqbal, Tabish; Atkinson, Megan; Vo-Le, Brittany; Vo-Le, Bylinda; O’Brien, Brittany; Grillon, Christian; Swann, Alan C.; Mathew, Sanjay J. (Frontiers in Psychiatry, 2019)
Background: Individuals with post-traumatic stress disorder (PTSD) have a heightened sensitivity to subsequent stressors, addictive drugs and symptom recurrence, a form of behavioral sensitization. N-methyl-D-aspartate receptors (NMDARs) are involved in the establishment and activation of sensitized behavior. Objective: We describe a protocol of a randomized placebo-controlled Phase 1b proof-of-mechanism trial to examine target engagement, safety, tolerability, and possible efficacy of the NMDAR antagonist lanicemine in individuals with symptoms of PTSD (Clinician Administered PTSD Scale [CAPS-5] score ≥ 25) and evidence of behavioral sensitization measured as enhanced anxiety-potentiated startle (APS, T-score ≥ 2.8). Methods: Subjects (n=24; age range 21-65) receive three 60-min intravenous infusions of placebo or 100 mg lanicemine over 5 non-consecutive days. Primary endpoint is change in APS from pre-treatment baseline to after the third infusion. NMDAR engagement is probed with resting state EEG gamma band power, 40Hz auditory steady state response, the mismatch negativity amplitude, and P50 sensory gating. Change in CAPS-5 scores is an exploratory clinical endpoint. Bayesian statistical methods will evaluate endpoints to determine suitability of this agent for further study. Conclusion: In contrast to traditional early-phase trials that use symptom severity to track treatment efficacy, this study tracks engagement of the study drug on expression of behavioral sensitization, a functional mechanism likely to cut across disorders. This experimental therapeutics design is consistent with recent NIMH-industry collaborative studies, and could serve as a template for testing novel pharmacological agents in psychiatry.